Penile Synovial Sarcoma: Clinical and Radiological findings - Espinoza-Figueroa, Jossué (2020)
A 22-year-old man presented with a 6-month-old 8 cm hard tumor at the base of the penis, whose biopsy was consistent with synovial sarcoma (Figure 1). The magnetic resonance imaging (MRI) showed a tumor that compromises the base of the penis, the left pillar and partially the right pillar, extending to the distal 2/3, without ruling out urethral infiltration (Figure 1).